Corner compensation mask design on (MEMS) accelerometer structure - Norliana, Yusof; Che Wan Noorakma, Abdullah; Norhayati, Soin (2014)
This paper presents the analysis effect of etching temperature and KOH concentration on convex corner undercutting of (MEMS) accelerometer structure. The lntellisuite CAD simulation software was used for the simulation analysis. From the analysis it was found that the optimum etching condition for this convex comer was at 25 wt% KOH concentration and 63'C etching temperature. Different types of compensation mask comers were designed which are comer, square and triangle in order to study the undercutting phenomena. In this case, the square corner compensation mask was chosen as it shown the most suitable compensation mask for this design of accelerometer. The etching simulation was continued with square corner compensation mask etched in the optimized temperature and KOH concentration and it indicated that the square corner compensation mask is the most suitable mask to solve the convex corner undercutting for this accelerometer structure.